Feasibility trial of an unguided ultra-brief online psychological intervention within an online mental health clinic: The “things you do” intervention - Ram P. Sapkota; Alayna Gretton; Andrew Wilhelms; Madelyne A. Bisby; Blake Dear; Nick Titov; Heather D. Hadjistavropoulos (Internet Interventions)
This feasibility study evaluated the acceptability and effectiveness of the Things You Do (TYD) intervention within a routine online therapy clinic. The TYD intervention is an ultra-brief unguided online intervention targeting symptoms of depression and anxiety by promoting engagement in empirically supported thoughts and behaviors (actions). It is comprised of one lesson, two worksheets and automated daily email reminders for one month. In total, 73 out of 112 help-seeking individuals completed the TYD intervention after being enrolled, and of these 48 completed one or more assessments at 2-, 4- or 16-weeks follow-up. weeks. High rates of participant satisfaction were observed among 30 participants who completed the satisfaction questionnaire. Qualitative comments suggested participants valued the daily email reminders, practical techniques and accessible content but some participants found the intervention too short or generic. Linear mixed-effects models examining within-group changes found significant reductions in depression (d = 0.80) and anxiety (d = 0.65) from pre- to post-intervention, with effects maintained at follow-up. Participation in the intervention was significantly associated with increased engagement in adaptive behaviors (d = 0.61), which, in turn, was linked to greater symptom improvement. Preliminary findings support the feasibility, acceptability and potential effectiveness of the TYD intervention as an accessible, ultra-brief unguided online intervention for anxiety and depression that may be valuable for some individuals seeking services from an online mental health clinic. Future research should explore its efficacy compared to control conditions among diverse populations and tailoring of content to participants.